PERBANDINGAN METODE STANDAR NASIONAL INDONESIA DAN NON STANDAR NASIONAL INDONESIA DALAM PENENTUAN KADAR KARBOHIDRAT TOTAL - Nurfadilah Nurfadilah; Anton Yuntarso; Dheasy Herawati (Jurnal SainHealth, 2019)
Carbohydrates are a source of energy needed by the body because carbohydrates are an important food component. According to SNI (Standar Nasional Indonesia), carbohydrate content in food must not be less than 60%. In this study, researchers wanted to compare the method of determining carbohydrate content according to SNI and according to AOAC (Non-SNI), both methods used Luff Schoorl, in the SNI method there was an addition of CH3COOH, whereas the Non-SNI method did not add CH3COOH. In this study a sample of a mixture of glucose, sucrose and NaCl was used. From the research results obtained indicate that there is a difference between the SNI method and Non-SNI method, where the Non-SNI method is better used at a 10% sample concentration with 250X dilution and 20% sample concentration at 500x dilution, whereas on the SNI method is better used at 30% sample concentration with 500X dilution, and the accuracy value obtained is 94.14% to 97.23%.